THE RUSSIAN STATE, LENIN AND THE CENTRAL ASIA - E. M. Korhzokin (Vestnik MGIMO-Universiteta)
Central Asian nations faced a challenge of state-building objectives after the collapse of the USSR. However, it was a complicated task, because those nations were parts of the Russian and, lately, the Soviet state. State-building objectives include the creation of new historical narrative. Central Asia is now experiencing the process that is called "national novel" in the Western European historiography. Central Asian national variants of historical narratives serve as a conceptual basis for the writing of school and university textbooks. The introduction of ideological constructs through the education system is carried out everywhere. However, it is important to note that inevitable ideological indoctrination should not undermine scientific essence of textbooks. Politics of nation formation and the preservation of its identity is implemented and fostered by states carefully as well as clumsy. There is no doubt that there is an inevitable and practical need for constructing "national novel" in the new states. But historical politics should not ignore some of the methodological and at the same time mental traps that exist in the field of studying the history of the peoples of Central Asia in the period of the Russian Empire.